Perbanyakan Tanaman Penutup Tanah Mucuna bracteata L. Melalui Skarifikasi Benih Secara Mekanis - Novalia Siti Ramadani Sinaga; Siti Hartati Yusida Saragih; Kamsia Dorliana Sitanggang (UNIVERSITAS LABUHANBATU, 2026)
Mucuna bracteata is a type of legume commonly used as a ground cover plant in oil palm plantations. This plant is useful for reducing weeds, increasing soil fertility, and improving soil structure through nitrogen fixation. However, Mucuna bracteata seeds have a very hard, impermeable shell, which prevents water from entering the embryo and slows down the germination process. The purpose of this study was to examine how mechanical scarification of seeds can improve their germination capacity. Mechanical scarification was carried out by damaging the tip of the seed until the white flesh was visible. Observations were made for 4 weeks after planting and included the percentage of germination, plant vine length, and number of leaves. The results showed that scarification accelerated and increased the seed germination rate by 30%. However, its effectiveness in breaking the dormancy of all seeds was still low, so additional methods or combinations of other treatments are needed to achieve higher germination rates. Keywords: Mucuna Bracteata, Mechanical Scarification, Germination